Peningkatan Hasil Belajar PKn Melalui Model Pembelajaran Talking Chips - Sinurat, Yahya (JURNAL PENA EDUKASI, 2018)
Abstract: The study aims to determine whether learning Talking Chips can improve student learning outcomes on the subjects of Civics grade IV SD Negeri 016528 BP. Mandoge academic year 2015/2016. The subject of this research is the fourth grade students of SD Negeri 016528 BP. Mandoge with 41 people. This research method is pre-test and post-test experimental group. From pengelolahan data obtained the average score obtained by students on the first cycle of 64.39. Of the 41 students, 24 students (58.54%) were completed in study while 17 students (41.46%) had not yet completed their study. Then on the second cycle there is an increase in the average value to 77.32. Of the 41 students, 35 students (85.37%) have experienced learning completeness, while 6 more students (14.63%) have not succeeded. Based on the increase of value starting from the initial test, cycle I and cycle II can be said that by using Talking Chips learning model can improve student learning outcomes in class IV SD Negeri 016528 BP. Mandoge on Civics subject matter of central government system Keywords: talking chips, government, central government Abstrak: Penelitian bertujuan untuk mengetahui apakah pembelajaran Talking Chips dapat meningkatkan hasil belajar siswa pada mata pelajaran PKn kelas IV SD Negeri 016528 BP. Mandoge Tahun Pelajaran 2015/2016. Subjek penelitian ini adalah siswa kelas IV SD Negeri 016528 BP. Mandoge dengan jumlah 41 orang. Metode penelitian ini adalah pre-test dan post-test eksperimental group. Dari pengelolahan data diperoleh hasil nilai rata-rata yang diperoleh siswa pada siklus I sebesar 64,39. Dari 41 siswa, 24 orang siswa (58,54%) telah tuntas dalam belajar sedangkan 17 orang siswa (41,46%) belum tuntas dalam belajar. Kemudian pada siklus II terjadi peningkatan nilai rata-rata menjadi 77,32. Dari 41 orang siswa, 35 orang siswa (85,37%) telah mengalami ketuntasan belajar, sedangkan 6 orang siswa lagi (14,63%) belum berhasil. Berdasarkan peningkatan nilai mulai dari tes awal, siklus I dan siklus II dapat dikatakan bahwa dengan menggunakan model pembelajaran Talking Chips dapat meningkatkan hasil belajar siswa di kelas IV SD Negeri 016528 BP. Mandoge pada mata pelajaran PKn materi sistem pemerintahan tingkat pusat Kata kunci: talking chips, pemerintah, pemerintahan tingkat pusat